2012
DOI: 10.1371/journal.pone.0041081
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Animal Welfare within a Reintroduction: An Assessment of Different Indices of Stress in Water Voles Arvicola amphibius

Abstract: Reintroductions are an increasingly common conservation restoration tool; however, little attention has hitherto been given to different methods for monitoring the stress encountered by reintroduced individuals. We compared ten potential measures of stress within four different categories (neuroendocrine, cell function, body condition and immune system function) as proxies for animal welfare in water voles being reintroduced to the Upper Thames region, Oxfordshire, UK. Captive-bred voles were assessed pre-rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 48 publications
(74 reference statements)
0
17
0
Order By: Relevance
“…Examples include body condition, weight, coat, plumage or skin condition, injury or pathology, altered gait or the occurrence of abnormal behaviors [e.g., ( 26 , 84 , 87 – 90 )]. Likewise, blood, saliva and fecal components indicating nutritional status or energy reserves, immune or reproductive function or “stress” may be evaluated [e.g., ( 13 , 91 94 )]. In rehabilitation, translocation and reintroduction contexts, when animals are under closer human control for longer periods, clinical examinations may be performed to evaluate the health status and potential survivability of rescued, captured or captive wild animals [e.g., ( 35 , 95 – 100 )].…”
Section: Conception Of Animal Welfare Influences Its Evaluation and Ementioning
confidence: 99%
See 2 more Smart Citations
“…Examples include body condition, weight, coat, plumage or skin condition, injury or pathology, altered gait or the occurrence of abnormal behaviors [e.g., ( 26 , 84 , 87 – 90 )]. Likewise, blood, saliva and fecal components indicating nutritional status or energy reserves, immune or reproductive function or “stress” may be evaluated [e.g., ( 13 , 91 94 )]. In rehabilitation, translocation and reintroduction contexts, when animals are under closer human control for longer periods, clinical examinations may be performed to evaluate the health status and potential survivability of rescued, captured or captive wild animals [e.g., ( 35 , 95 – 100 )].…”
Section: Conception Of Animal Welfare Influences Its Evaluation and Ementioning
confidence: 99%
“…For example, it is well-established that dairy cattle, pigs and poultry which are more fearful of their human handlers exhibit lower productivity and/or reproductive success than their less fearful cohorts ( 134 ). This advancing biological understanding and evidence facilitates cautious interpretation of the kinds of data already collected in some conservation research as reflecting the mental experiences of the animals and thus their welfare state, e.g., hydration status or changes in body condition ( 94 ) as indicators of thirst and hunger, respectively ( 132 ).…”
Section: Conception Of Animal Welfare Influences Its Evaluation and Ementioning
confidence: 99%
See 1 more Smart Citation
“…The objective of the present study was to discover novel animal-based biomarkers and evaluate well-known existing ones based on transcriptome profiling and to derive inferences about the onset of suggestive pathways. The combination of different techniques, which allow quantifying multiple parameters with relevance to distinct stress responses, is established as a promising approach to assess the individual welfare status 53 . The present study was based on the recording of primary (cortisol level), secondary (glucose level, haematocrit, leukocyte count, gene expression) and tertiary (condition factor, spleen-somatic index, cellular immune competence) stress indicators.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies are few, our results add to the general reported trend of resilience to translocation and/or translocation stress in reptiles. In contrast, several studies in mammals and birds have reported significant long-term effects of ­translocation on CORT secretion ( Franceschini et al ., 2008 ; Dickens et al ., 2009 ; Zidon et al ., 2009 ; Gelling et al ., 2012 ; Jachowski et al ., 2013 ). However, this observation is not consistent, because other studies have reported no long-term effect ( Hartup et al ., 2005 ; Adams et al ., 2013 ; Bosson et al ., 2013 ; Ji et al ., 2013 ), suggesting that adaptation to new environments (indicated by long-term CORT secretion) is species specific or context dependent (e.g.…”
Section: Discussionmentioning
confidence: 99%